Knowledge about Breast Cancer and Breast Self Examination Practices among Medical, Dental and B.Sc Nursing Students of BPKIHS - Parajuli, Puspa; Mandal, GN (Health Renaissance, 2011)
The aim of this descriptive cross sectional study was to assess knowledge about breast cancer and breast self examination practices among medical, dental and B.Sc nursing students and to identify the associated factors which influence towards the breast self examination (BSE). The survey was conducted among 220 graduate levels female students by using non probability convenience sampling technique. Mean knowledge about the breast cancer, as indicated by the results were 63.67±16.22, 71 ±18.16 and 76 07 ±18.60 among BDS, B.SC nursing and MBBS students respectively. Similarly mean practices regarding BSE were found to be 34.67 ± 15. 41, 47.85 ±14.08 and 46.76 ±14.77 among BDS, B.Sc nursing and MBBS respectively. Knowledge was less among BDS students whereas, it was found quite higher in MBBS and B.Sc nursing students. Similarly, mean practice in relation to BSE was found to be low in BDS, high in B.Sc nursing, and higher in MBBS students. Overall level of knowledge was found to be mordantly adequate among all disciplines, however practices among them were found to be inadequate. Keywords: knowledge; practices; breast cancer; breast self examination; medical; dental and B.Sc Nursing students. DOI: 10.3126/hren.v8i3.4209 Health Renaissance, September-December 2010; Vol 8 (No.3);166-168